Training on the Production of Biowash Derak at SMAN 3 Muaro Jambi : Pelatihan Pembuatan Biowash Derak (Detergen Organik Berbahan Dasar Lerak) di SMAN 3 Muaro Jambi - Destiana, Anggari Linda; Nugraha, Anggit Prima; Husnudin, Uni Baroroh; Maritsa, Hasna Ul; Mulyani, Putri Dwi; Yusuf, Ashif Irvan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The lerak fruit (Sapindus rarak) possesses significant potential as a natural detergent that can serve as an alternative to chemical-based detergents, which are increasingly concerning due to their detrimental effects on the environment and their impact on soil and aquatic organisms. The saponin content in lerak generates foam and exhibits antibacterial properties, making it environmentally safe for both soil and aquatic life. The objective of this program is to train students and teachers at SMAN 3 Muaro Jambi in producing natural detergent from lerak, thereby supporting extracurricular batik activities while also contributing to the establishment of an environmentally friendly school. The stages of this community service activity include socialization, hands-on training, and evaluation (pre- and post-tests). The results of the satisfaction measurement indicate that all participants were satisfied with the implementation of this community service, with 44.4% expressing high satisfaction and 55.6% being satisfied. The percentage of participant's knowledge regarding the name, benefits, preparation methods, and usage of lerak increased by 86%. The number of participants capable of producing lerak detergent rose significantly, from 4.7% to 85.4%, representing an increase of 80.7%. Overall, all participants expressed satisfaction with this activity and demonstrated an enhancement in their knowledge.